Les professionnels du bâtiment face aux enjeux énergétiques, une perspective limitée - Jonathan Villot (Éditions en environnement VertigO, 2015)
This paper deals with the dynamic of French building’s actors facing to energy and environmental issues. Based on a research on a specific target area (Loire department), the study aims to assess the state of the system and the limitations or barriers encountered by human and technical actors. Using the analysis of qualitative and quantitative results from actors’ surveys, the research reveals a variety of situations, barriers (some known but rarely quantified) and palliative’s solutions. Finally, the building sector reveals itself ineffective to move towards a new energy perspective without a total breakdown of his ways of thinking and acting. This breakdown requires a perfect rationality of actors and especially that of public power.